2016
DOI: 10.1016/j.exphem.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA panel for prediction of acute graft-versus-host disease in lymphoma patients undergoing matched unrelated hematopoietic stem cell transplantation

Abstract: Acute graft-versus-host disease (aGVHD) results in significant morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Noninvasive diagnostic and prognostic tests for aGVHD are currently lacking, but would be beneficial in predicting aGVHD and improving the safety of allo-HSCT. Circulating microRNAs exhibit marked stability and may serve as biomarkers in several clinical settings. Here, we evaluated the use of circulating microRNAs as predictive biomarkers of aGVHD in lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 49 publications
1
41
1
Order By: Relevance
“…Although previous groups have performed microRNA profiling post-HSCT, these studies have focused on specific subgroups of patients or a refined signature of microRNAs limited by the qRT-PCR technology used (13, 17). This study was based on NanoString technology, which incorporates over 700 validated microRNA targets allowing for the most comprehensive assessment of circulating microRNA expression in a HSCT setting to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous groups have performed microRNA profiling post-HSCT, these studies have focused on specific subgroups of patients or a refined signature of microRNAs limited by the qRT-PCR technology used (13, 17). This study was based on NanoString technology, which incorporates over 700 validated microRNA targets allowing for the most comprehensive assessment of circulating microRNA expression in a HSCT setting to date.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have assessed expression of specific circulating microRNAs in the serum or plasma of patients post-HSCT to identify potential biomarkers for aGvHD incidence, severity, or outcome (1317), and some investigations have included profiling of an extended microRNA repertoire (13, 17). However, these studies have focused on a subset of microRNAs that can be detected by high-throughput qRT-PCR-based arrays (13, 17) or within specific subsets of patients such as lymphoma patients receiving matched unrelated donor (MUD) allo-HSCT (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study, Gimondi et al focused on lymphoma patients receiving MUD allo-transplants to profile the plasma using qRT-PCR for global miRNA expression (94). Assessing samples collected 28 days post-HSCT, 113 miRNAs were detected in all samples and of these, 27 could collectively discriminate between aGvHD versus no aGvHD and miRNA-194 and miRNA-518f were significantly upregulated in the patients who later developed the disease (94).…”
Section: Soluble Biomarkersmentioning
confidence: 99%
“…Assessing samples collected 28 days post-HSCT, 113 miRNAs were detected in all samples and of these, 27 could collectively discriminate between aGvHD versus no aGvHD and miRNA-194 and miRNA-518f were significantly upregulated in the patients who later developed the disease (94). The authors did not detect differential expression of miRNAs identified by Xiao et al (92), and there was no validation cohort included in the investigation.…”
Section: Soluble Biomarkersmentioning
confidence: 99%